A lei e a força no regime militar brasileiro: da proscrição da frente ampla à edição do Ato Institucional n. 5 - Del Vecchio, Angelo [UNESP] (My University, 2013)
This article analyses the Brazilian political process in the period between the beginning of the government of general Arthur da Costa e Silva in March 15, 1967 and the edition of the Institutional Act No. 5 (December 13, 1968). Through the analysis of the key moments in this context, seeks to qualify the actions of the main political players in terms of their goals and strategies and assess the impact that they had on the production of authoritarian legislation.

O presente artigo aborda o processo político brasileiro no período compreendido entre a posse do general Arthur da Costa e Silva na presidência da República, em 15 de março de 1967 e a edição do Ato Institucional no. 5 (13 de dezembro de 1968). Através da análise dos principais momentos desse contexto, busca-se qualificar as ações dos principais agentes políticos em termos de seus objetivos e estratégias e avaliar as repercussões que as mesmas tiveram na produção da legislação autoritária.
The law and the strength in brazilian military regime: to the bans of the broad front for institutional act n. 5
Keywords: Policy; Military regime; Authoritarian legislation; Elite military leader; Política; Regime militar; Legislação autoritária; Elite militar dirigente